Factors Affecting Post-Retirement Working Demand and Attitude Toward Work of Nearly Retired Workers in Chiang Mai Province - Arkornsakul, Pacharaporn (Journal of Applied Economics and Management Strategy, 2023)
This research aimed to (1) analyze factors affecting the post-retirement working demand of the nearly retired workers in Chiang Mai province, and (2) study the attitude toward work of nearly retired workers in Chiang Mai province. The samples were 400 nearly retired workers aged between 55 to 59 years old. The data were collected by using questionnaires and analyzed by Logit Model. The results showed that the factors affecting the post-retirement working demand of the nearly retired workers in Chiang Mai province were education level, number of household members, monthly income, and liabilities. Factors like gender, age, marital status, financial support for children, and health status were not statistically significant in this study. For the attitudes toward work of nearly retired workers in Chiang Mai province, it was found that most of the nearly retired workers preferred half-time employment and would like the government to set the new wage rates for elderly workers. Moreover, the nearly retired workers agreed with the government’s measures to promote employment among the elderly to ensure economic security given insufficient welfare from the government.